The Life and Pontificate of Pope Pius Xii - Coppa, Frank J. (Book collections on Project MUSE., 2013)
Eugenio Pacelli, Pope Pius XII, is one of the most studied but least understood popes of the twentieth century, while his pontificate remains the most turbulent and controversial. Although there is a general consensus that he faced serious problems during his tenure - fascist aggression, the Second World War, the Nazi genocide of the Jews, the march of communism, and the Cold War - there is disagreement on his response to these developments. Applauded by some as an "apostle for peace" for his attempt to prevent the outbreak of war, he has been denounced by others as an "advocate of appeasement" for this same effort. Praised by both Christian and Jews for his "Crusade of Charity" during the war, he was denounced by many for his silence during the Holocaust. These conflicting interpretations, dubbed the Pius Wars, are often narrow in focus, lack objectivity, and have shed more heat than light. Written by one of the foremost historians of Pius XII, this biographical study, unlike the greater part of the vast and growing historiography of Pope Pius XII, is a balanced and nonreactive account of his life and times. Its focus is not on the pope's silence during the Holocaust, though it does address the issue in a historical and objective framework. This is a biography of the man as well as the pope. It probes the roots of his traditionalism and legalism, his approach to modernity and reformism in Church and society, and the influences behind his policies and actions. This book is the first biography of Eugenio Pacelli to appear in English since the opening of the papers of the pontificate of Pius XI (1922-1939), in which Pacelli served as nuncio to Germany and secretary of state, along with the publication of the memories of figures close to Papa Pacelli. -- Publisher's description.